2012
DOI: 10.1108/17554251211200428
|View full text |Cite
|
Sign up to set email alerts
|

Modelling bi‐directional research: a fresh approach to stakeholder theory

Abstract: PurposeWhile Freeman's stakeholder management approach has attracted much attention from both scholars and practitioners, little empirical work has considered the interconnectedness of organisational perspectives and stakeholder perspectives. The purpose of this paper is to respond to this gap by developing and empirically testing a bi‐directional model of organisation/stakeholder relationships.Design/methodology/approachA conceptual framework is developed that integrates how stakeholders are affected by organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…A particular contribution of this paper is the evidence it provides substantiating the bi-directional modelling approach to stakeholder theory proposed by Money et al (2012) and MacMillan et al (2000); this is shown to be particularly appropriate to understanding the roles of the three relational factors in the context of Sino-foreign joint ventures.…”
mentioning
confidence: 74%
“…A particular contribution of this paper is the evidence it provides substantiating the bi-directional modelling approach to stakeholder theory proposed by Money et al (2012) and MacMillan et al (2000); this is shown to be particularly appropriate to understanding the roles of the three relational factors in the context of Sino-foreign joint ventures.…”
mentioning
confidence: 74%
“…following Money et al (2012b), outcomes of CR will be categorised in terms of a hierarchy that starts with affective outcomes (such as trust and positive emotions); moves to maintaining behaviours (such as staying in a relationship); and then moves to expanding behaviours that require discretionary effort (such as advocacy). This categorisation builds upon insights from psychology literature, which suggest that behaviour change is often slow and builds in increments from the current expression of behaviour (e.g.…”
Section: The Need For Better Categorised Outcomes Of Cr -Speaks To Inmentioning
confidence: 99%
“…These drivers are also well established in research and categorisation of stakeholder experiences is in terms of relational aspects such as experiences related to how well organisations inform, listen, keep commitments and provide benefits to stakeholders (e.g. Walsh et al, 2009b;Money et al, 2012b) -as well as more negative experiences that relate to the use or abuse of power by organisations (e.g. MacMillan et al, 2004;Money et al, 2012b).…”
Section: The Need For a Wider Range Of Causes Of Cr -Speaks To Changimentioning
confidence: 99%
“…Reputation is active important for stakeholders, namely for workers and members of cooperative, but their role is crucial to the organization's reputation [62,63]. "Report framework" and "report process" can be adapted and applied to different situations to achieve mutually rewarding and harmonious exchanges between organizations and stakeholders in line with the vision of many stakeholder theorists [64].…”
Section: Models Bimentioning
confidence: 99%